A systematic review and meta-analysis of acoustic stimulation in the treatment of insomnia - Wang, Mengchen; Fan, Shuai; Wang, Zixu; Ren, Jixiang (Frontiers in Neuroscience, 2025)
BackgroundInsomnia is a prevalent and debilitating sleep disorder affecting approximately one-third of the global population, with 10–15% of individuals progressing to chronic insomnia. Acoustic stimulation, a promising non-pharmacological treatment, has gained significant attention due to its ability to improve sleep quality without the adverse effects of drugs. This study aims to evaluate the clinical efficacy of acoustic stimulation for treating insomnia through a systematic review and meta-analysis.MethodsWe conducted a systematic search of both Chinese and English literature from PubMed, Embase, Web of Science, Cochrane, and Clinical Trials databases to identify randomized controlled trials (RCTs) evaluating acoustic stimulation for insomnia. The search period ranged from the establishment of the database to January 1, 2025. Two independent evaluators assessed study quality and extracted relevant data. Statistical analyses were conducted using RevMan 5.4 and Stata 18.0 software.ResultsThis meta-analysis includes 8 studies involving 419 patients. The results showed that acoustic stimulation significantly improved insomnia severity as evidenced by PSQI and ISI scores. Despite no significant improvement in sleep efficiency (SE) and Total sleep time (TST), acoustic stimulation notably increased total sleep time and alleviated insomnia symptoms. The test group demonstrated significant improvements compared to the control group, with the following outcomes: PSQI score [MD = -2.68, 95% CI (-3.35, -2.01), P < 0.00001] and ISI score [MD = -2.26, 95% CI (-4.09, -0.43), P = 0.02].ConclusionAcoustic stimulation is an effective and safe treatment for insomnia, offering significant improvements in sleep quality, severity, and overall health, with minimal side effects. It presents a promising alternative to traditional pharmacological treatments, especially for long-term use, and its clinical application has broad prospects. Future studies should focus on expanding sample sizes, exploring various stimulation methods, and considering individual patient characteristics for more detailed analyses.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025632371, identifier CRD42025632371.